Can you get a job doing that?: Reimagining the Arts - Earnest L Lamb (Academic Chairpersons Conference Proceedings, 2017)
Arguably the significance of a college degree is determined by the value it has in the market place. Rather than a critique of the commodification of education, this session offers strategies for the leadership in the arts and humanities to reimagine their programs in ways that will prepare their graduates for careers in and outside of the academy.
Keywords: arts; humanities; commodification of education; leadership